Changing scenery: Historicity in the Area of Lake Hjälmaren, Sweden, c. 2800-2300 BC - von Hackwitz, Kim (Current Swedish Archaeology, 2008)
The article addresscs changes in the archacological record during the Middle Neolithic B in the area of Lake Hjälmaren. The main focus is on the difference between the Pitted Ware sitcs and thc Boat-Axe sites with regard to choice of location. Traditionally the different distributions ofthesc two assemblages have been understood as designating two different and more or less contcmporaneous "cultures". An alternative view to the conventional understanding is that the material cultures represent use and re-use activities associated with different spaces in thc landscape. In thc author’s opinion, the choices and activities that constitute these spaces should be understood as reflecting activities that took place in relation to a pre-existing landscape. In order to describe and analyse the relationship, the author applies theories ofhistoricity and landmark, pointing towards an active social reproduction of a landscape.